Cognitive performance’s critical role in the progression from educational attainment to moderate to vigorous physical activity: insights from a Mendelian randomization study - Qi, Fang; Jinmin, Zhang (Frontiers in Psychology, 2024)
In individuals with high educational levels, moderate to vigorous physical activity (MVPA) is often elevated, yet the causal direction and the role of cognitive performance in this association remain ambiguous. The purpose of this study was to analyze the causal effects of educational attainment on MVPA levels and to explore potential mediating factors.Methods: Two-sample univariate MR analysis was conducted to assess the overall effect of education on moderate to severe physical activity. Besides, a two-step MR analysis was carried out to evaluate the mediating effect of cognitive performance on the impact of education on MVPA. Individuals included were exclusively of European ancestry, with data gathered from extensive genome-wide association studies (GWAS) on education (n=470,941), cognitive performance (n=257,841), and MVPA (n=377,234). Educational attainment was measured by college graduation status. Cognitive performance encompasses psycho-motor speed, memory, and abstract reasoning abilities. MVPA is defined as any physical activity that produces a metabolic equivalent (MET) of ≥3.0.The positive two-sample MR analysis showed that education level had a significant protective effect on MVPA deficiency (β= -0.276, 95% CI=-0.354 to -0.199, p=2.866 × 10 -12 ). However, the reverse two-sample MR analysis showed that MVPA had no significant causal relationship with education level (p=0.165). Subsequently, the two-step MR analysis indicated that the potential causal protective effect of education on the risk of MVPA deficiency was mostly mediated by cognitive performance (mediating effect β=-0.235,95% CI=-0.434 to -0.036, and the intermediary ratio was 85.061%).Discussion: Cognitive performance holds considerable significance in the relationship between education level and MVPA.